New Trends in Russian Intellectual Anti-Americanism: The Strange Case of Viktor Pelevin's Novel S.N.U.F.F. (May 2014) - Lalo, Alexei
<x content-type="archive" xml:space="preserve">Abstract</x> Victor Pelevin's 2011 novel S.N.U.F.F. is discussed in terms of being a dystopia and a Menippean satire, as well as an anatomy of today's cultural interactions between Russia and the West. Pelvin's consistent approach in constructing an elaborate critique of U.S. cultural imperialism is examined in relation to the expansion of popular culture, and also through a Eurocentric epistemological hegemony in the context of which U.S. leftist–liberal academics teach the non-Western 'rest of the world' what such things as gender, race, homo- and heterosexuality, femininity, masculinity, sexism, hate speech, etc., should mean in one's respective culture. The vast, panoramic satirical canvas of intellectual attitudes and cultural beliefs that Pelvin has drawn is described as an attempted worldwide 'colonization of the mind', which has today become an avatar of cultural Americanization.